2014
DOI: 10.1167/iovs.14-15046
|View full text |Cite
|
Sign up to set email alerts
|

Does Cigarette Smoking Alter the Risk of Pterygium? A Systematic Review and Meta-Analysis

Abstract: The results of this meta-analysis show that cigarette smoking was associated with a reduced risk of pterygium, especially in current smokers. This effect may be independent of UV exposure and sex. Investigations are needed to unveil its molecular basis serving therapeutic purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 56 publications
3
30
1
Order By: Relevance
“…18 However, this analysis was mainly based on cross-sectional or case-control studies (of the 24 studies, 22 were cross-sectional or case-control studies). Our study together with the other 2 longitudinal cohort studies did not support this conclusion, indicating that the association in the meta-analysis may be spurious.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 However, this analysis was mainly based on cross-sectional or case-control studies (of the 24 studies, 22 were cross-sectional or case-control studies). Our study together with the other 2 longitudinal cohort studies did not support this conclusion, indicating that the association in the meta-analysis may be spurious.…”
Section: Discussionmentioning
confidence: 99%
“…14 For environmental factors, exposure to ultraviolet radiation is the most consistent risk factor, which may result in cellular changes in the medial limbus of the cornea. [2][3][4]6,[15][16][17] Smoking has been linked with a reduced risk of pterygium, 18 but this observation could not be replicated in longitudinal analysis. 12 Some sporadic studies also reported that blood pressure, 3 cholesterol level, 3 or fasting blood glucose concentration 12 were associated with the risk of pterygium, but these associations have not been confirmed.…”
mentioning
confidence: 99%
“…We included only studies with five or more stars. The modified Estabrooks’ tool for cross-sectional studies contains 14 items in two groups 39. Group I includes the probabilistic sample used, sample size appropriate for power, response rate exceeding 50%, validity, appropriate tests used and CI reported.…”
Section: Methodsmentioning
confidence: 99%
“…Group II includes representative sample, sample drawn from multiple sites, cluster/stratified design, multiple adjusted, detective variable (primary outcome) directly measured/administrative, reliability, p values reported and missing data managed appropriately. A study was considered to be of high risk of bias when one item in Group I was marked as ‘No’ or two items marked as ‘N/A’, or any two items from Group II were marked as ‘No’ or three items marked as ‘N/A’ 39. Articles with high risk of bias were excluded from the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Agents utilized to inhibit recurrence such as mitomycin C, 5-fluorouracil or triethylene thiophosphoramide were not used in any of the cases. 15,16,17 The conjunctival grafts were positioned leaving no open scleral tissue starting from the nasal and temporal limbus, with the epithelial side up and the limbal area aligned with the limbus. Both grafts were sutured to the surrounding conjunctiva with a shallow pass through the episclera using 8/0 vicryl (Figure 2).…”
Section: Methodsmentioning
confidence: 99%